2019
DOI: 10.1093/infdis/jiz668
|View full text |Cite
|
Sign up to set email alerts
|

Men and Women Have an Equal Oropharyngeal and Anorectal Chlamydia trachomatis Bacterial Load: A Comparison of 3 Anatomic Sites

Abstract: Background The Chlamydia trachomatis bacterial load could have impact on transmission and sequelae. This is the first study providing comparison of C. trachomatis load at 3 anatomic sites estimated by cycle quantification (Cq) values. Methods Data from 7900 C. trachomatis-positive samples were included (2012–2018). Cq value was used as an inversely proportional measure for C. trachomatis load. Multivariable linear regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…12,25 Spontaneous pharyngeal C trachomatis clearance has been estimated to be 36-57% within a median time of 9-10 days, 14,12,25 and this proportion seems to be higher than for genital or rectal infections. 12,[26][27][28] The percentage viable in pharyngeal C trachomatis samples (26%) has been much lower than in genital (94-96%) or rectal (58-67%) positive samples. 14.23 Regarding the public health effect, some evidence suggests that pharyngeal C trachomatis might contribute to ongoing transmission to sexual partners.…”
Section: Discussionmentioning
confidence: 99%
“…12,25 Spontaneous pharyngeal C trachomatis clearance has been estimated to be 36-57% within a median time of 9-10 days, 14,12,25 and this proportion seems to be higher than for genital or rectal infections. 12,[26][27][28] The percentage viable in pharyngeal C trachomatis samples (26%) has been much lower than in genital (94-96%) or rectal (58-67%) positive samples. 14.23 Regarding the public health effect, some evidence suggests that pharyngeal C trachomatis might contribute to ongoing transmission to sexual partners.…”
Section: Discussionmentioning
confidence: 99%
“…14 One recent large study found higher bacterial loads in rectal infections compared with pharyngeal infections and no differences between men and women tested but reported only cycle threshold levels. 15 Although it is difficult to define the precise number of bacteria needed to cause infections at these sites, the limit of detection for the Abbott RealTime CT/NG assay reported here would be expected to detect infections for the bacterial loads in those reports. The clinical performance of the Abbott RealTime CT/NG in rectal and pharyngeal specimens was recently evaluated in a multicenter study of 2598 symptomatic and asymptomatic patients, alongside two other assays that have now been FDA approved for detection of C. trachomatis and N. gonorrhoeae at rectal and pharyngeal sites.…”
Section: Discussionmentioning
confidence: 96%
“…6 The proportion of spontaneous clearance of oropharyngeal CT is much higher than we observed for vaginal CT (6.0%, 95% CI 4.2% to 8.4%) and rectal CT (15.8%, 95% CI 10.8% to 21.8%). 16 A possible explanation is the lower initial CT bacterial load at the oropharyngeal site compared with the vaginal and the rectal site, 7 because lower initial load is associated with oropharyngeal CT clearance. 6 8 Of those women who remained CT positive at the oropharyngeal site at week 0, three quarters had non-viable CT only.…”
Section: Discussionmentioning
confidence: 99%
“…6 Data on oropharyngeal CT in women are scarce as women are not routinely tested for oropharyngeal CT, while in MSM oropharyngeal testing is an emerging practice. 5 Oropharyngeal CT infections have been considered low bacterial load infections 7 that are frequently self-limiting. 6 8 Concerns were raised that oropharyngeal CT infection may initiate a reservoir of infection, that is, via the gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 99%